ANTI-CORRUPTION EDUCATION AT AN EARLY AGE AS A STRATEGIC MOVE TO PREVENT CORRUPTION IN INDONESIA - Ida Musofiana (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Corruption has become an extra ordinary crime, which is why many studies that discuss about corruption. Although many studies of corruption are able to find out the causes of corruption, by knowing the causes or factors of corruption is able to reduce corruption. In addition to the many studies of corruption, has also been a lot of coverage in both print and electronic media that presents news of the suspects or defendants involved in corruption cases, it is intended to give a lesson to the general public, as well as provide a deterrent effect so ashamed of corruption that has been done , but corruption is still frequently encountered. It is in fact considered normal by society. Further unrest arises how it affects young people who will be the successor to the ideals of the nation, that almost every time served reporting corruption is everywhere. Here the next question how so that the younger generation is not affected by the disease of corruption, should the anti-corruption legal education at an early age entered in learning in schools. Given the starting gate education acquired knowledge, insight and understanding for self-discovery. This paper will discuss the need for anticorruption education for children from an early age as a strategic move to prevent corruption in order to create a corruption-free Indonesia in 2020. From the results of research that has been done shows that the much needed anti-corruption education included in school subjects or courses at the college level are not only in the faculty of law. A proposal must be observed. Anti-corruption education materials could be inserted in the subjects of Pancasila, Citizenship, Mathematics, as well as career guidance, which includes the subject of honesty, discipline, and teach togetherness fighting spirit and simplicity. As all of which are meant to instill a sense of responsibility in a very important and settle obligations to completion. Combating corruption in developed countries are very intensively conducted are like in Singapore, which is implanted namely state hard ahead if the government does not free from corruption, prevention and repression of corruption through four things: effective anticorruption agency, effective acts, effective adjudication, and efficient administration , And all the pillars were motivated by the strong will pilitical against corription of government. As well as in Lithuania country. Key word : anti-corruption education, early age, prevention of corruption.